Efficacy of immune checkpoint inhibitors in different types of melanoma. Issue 1 (2nd January 2021) - Rossi, Ernesto; Schinzari, Giovanni; Maiorano, Brigida Anna; Indellicati, Giulia; Di Stefani, Alessandro; Pagliara, Monica Maria; Fragomeni, Simona Maria; De Luca, Erika Valentina; Sammarco, Maria Grazia; Garganese, Giorgia; Galli, Jacopo; Blasi, Maria Antonietta; et al.
ABSTRACT: Immunotherapy can be used for cutaneous, mucosal, uveal and conjunctival melanoma. Nevertheless, we cannot expect the same benefit from checkpoint inhibitors for all the types of melanoma. The different biological features can explain the variable efficacy. The main results obtained with immune checkpoint inhibitors in the various types of melanoma were reviewed.